Risk Factors, Level of Knowledge, and Scabies Transmission Prevention Behavior Among Students at the Ar-Rahmah Islamic Boarding School, Golokan, Sidayu, Gresik, Indonesia - Ramadhan, Rizaldy; Salsabila, Fatimah; Putri, Valensia; Shabirah, Fadhilah; Ramadhiansyah, Ghulam; Putri, Shafa; Malikulsaleh; Farhana, Hanan; Pratiwi, Cahya; Hefrida, Andriani; Djuari, Lilik (Universitas Airlangga, 2025)
Scabies is an infectious skin disease caused by the parasite Sarcoptes scabiei var. hominis and its products. Although the prevalence has decreased, scabies remains a public health problem in Indonesia. In the Sidayu District of Gresik, there has been an increase in scabies cases, particularly in densely populated communities such as Islamic boarding schools. Factors contributing to the high incidence of scabies are related to poverty, resulting in low levels of personal hygiene, limited access to water, and high population density. This study aims to determine the risk factors, level of knowledge, and scabies transmission prevention behavior among students at the Ar-Rahmah Islamic boarding school, Golokan Village, Sidayu District, Gresik, Indonesia in 2024. This research is a descriptive study, with data collected using a questionnaire. The sample comprises 88 respondents, selected through non-probability purposive sampling. Results showed that all respondents were male, 40.9% were 14 years old, 35.2% were in grade 8, and 34.1% had lived in an Islamic boarding school for 1-2 years. Additionally, all respondents had a level of housing density not meeting health standards, 79.5% had experienced scabies symptoms, and 56.8% had suffered from scabies. Furthermore, 55.7% of respondents demonstrated good knowledge about scabies, while 85.2% exhibited poor behavior in preventing scabies transmission, with 63.6% showing negative results when screened for scabies via questionnaire. Overall, most students exhibit high-risk factors for scabies, possess a good level of knowledge about the disease, yet demonstrate poor preventive behaviors against its transmission.